AN ANALYSIS POWER AND LOVE OF MAIN CHARACTER IN NOVEL “THE MOUNTAIN ECHOED”BY KHALED HOSSEINI - M. Asrul Hasby; Baiq. Zuhrotun Nafisah (Lembaga Penelitian dan Pendidikan Mandala, 2018)
This study was aimed to reveal the kind of power and love of the novel “The Mountains Echoed” by KhalledHosseini. The method on this study was qualitative descriptive. The data was obtained the kind of love and the power of love. It focused on analyzing kind love and power of love. The technique of collecting data used documentation technique, for library documentation studies, close-reading, identifying, and note taking, classifying in order to find out kind of love and power of love the novel The Mountains Echoed by Khalled Hosseini. The data analysis used qualitative descriptive particular data reduction, data displayed, conclusion, drawing and verification. There are three main concepts that will be used, first is the general theory of love by Thomas Lewis, FairiAmini, and Richard Lanmon, second is kinds of love by C.S Lewis, and the third is the concept of power and love by Adam Khane. To answer the statement of the problems, this study are using the concept of kinds of love that depicted by the characters in the novel. Description is used to describe the result of analysis. After getting through long analysis by using three kinds of method above, it can reveal the depiction of kinds of love that Affection depicted between Baba Ayub and Qais, Abdullah and Pari, and between; Friendship depicted between Abdullah and Markos, and between PariWahdati and Abdullah; Eros depicted between Abdullah and Parwana; and Charity, between Abdullah and Pari. Power and love depict by each kinds of love in their own way, unites or intentionally spares the two people, resembles the history of life, complete and walks together side by side